Development of Competency-Based Curriculum to Central Thai House Construction in Vocational Certificate Level - Punwatannakon, Shanaclunkanyakon; Ramwarungkura, Anuchai; Rakkusol, Nalinrat (Arts of Management Journal, 2025)
This objective of the research were to 1) study the competency of Central Thai House Construction in Vocational Certificate Level and 2) develop a competency-based curriculum for building Thai houses in the Central region at the vocational certificate level. The research is divided 2 phases. In phase 1, there are sub-phases as follows: 1.1) studies the feasibility of implementing the competency-based curriculum by using a questionnaire to school administrators and teachers. Data is analyzed using statistics, percentage, median, and standard deviation. 1.2) studies the competency by using the Delphi method, 17 people, which is a purposive selection. Data is analyzed using statistics, median, and interquartile range. In phase 2 develops a competency-based curriculum for building Thai houses in the Central region at the vocational certificate level by using group discussions with 7 experts, which is a purposive selection, and data is analyzed using content analysis. The results of Development of Competency-Based Curriculum to Central Thai House Construction in Vocational Certificate Level was included in the category of architectural technicians. Competencies were divided into 3 areas: knowledge 14 competencies; skills 12 competencies and attitude 9 competencies. From the group discussions, a short-term curriculum was obtained, consisting of 3 modules as follows: 1) Design and drafting of Central Thai houses 2) Production of workpieces, materials, and methods for constructing Central Thai houses 3) Building equipment, building maintenance, laws, and occupational health in Central Thai houses, which can be used in the curriculum at the vocational certificate level.